Efectos de fungicidas, químico y biologico en el control de tres enfermedades fungosas en el cultivo de cacao (Theobroma cacao L.) CCN 51- en la Parroquia Zapotal. - Solórzano Sabando, Ramón Antonio (2018)
The research is based on studying the effects of fungicides, chemical and biological in the control of three fungal diseases in the cultivation of cocoa (Theobroma cacao L.) CCN 51- in the zapotal parish whose objective is to evaluate the effect of chemical and biological fungicides in the control of three fungal diseases in the cultivation of cocoa (Theobroma cacao L.) CCN 51- in the Zapotal parish. For the distribution of the treatments in the field, the experimental design Completely Random Design (DCA) with three repetitions was used. To compare the means between treatments of the selected variables, the Duncan test was applied (p = 0.05). for which in situ tests were carried out with three fungicides: two chemical and one biological, Azoxystrobin, Copper Sulphate Pentahydrate and Trichoderma respectively, on the control of fungal diseases such as Moniliophthora roreri, Phytophthora spp and Moniliophthora perniciosa in cocoa (Theobroma cacao L.). The evaluations were made in the inhibition of diseases for each of the treatments. The records made were marked for each of the variables as follows. Fruits with attack of monilla, fruits with attacks of Phytophthora, fruits with attacks of broom of witch, fruits with cherelle wilt. The fungicides evaluated reached a 91.00% control of diseases, representing a total of 47.00 healthy fruits per plant, managing to suppress the disease by obtaining an incidence of 9.00% with 3 fruits on average per plant, far exceeding the control that showed an incidence of diseases of 62.00% equivalent to 33.00 ears per plant. The application of copper sulphate pentahydrate 1.00 l ha-1 generated greater control of affected ears with monilla, lowering the incidence of 3.00%, representing 2.00 ears per plant. The treatment with Trichoderma 1 * 109 spores per cm2 caused the greatest number of days to the appearance of the symptoms of the monilla with 83.00 days. Keywords: fungicides; Trichoderma; Moniliophthora roreri; Phytophthora spp